The case of the double trouble detectives - Preller, James; Smith, Jamie C. (New York : Scholastic, 2005)
Jigsaw Jones finds himself in competition with Reggie for the title of the best detective in town.
"A Little Apple paperback."
"RL2"--P. [4] of cover.
006-009.
470
Accelerated Reader AR
Keywords: Private investigators -- Fiction; Mystery and detective stories; Mystery fiction